Charcot‐Marie‐Tooth disease: frequency of genetic subtypes in a Southern Italy population. Issue 4 (December 2014) - Manganelli, Fiore; Tozza, Stefano; Pisciotta, Chiara; Bellone, Emilia; Iodice, Rosa; Nolano, Maria; Geroldi, Alessandro; Capponi, Simona; Mandich, Paola; Santoro, Lucio
Abstract The objective of this study is to assess the genetic distribution of Charcot‐Marie‐Tooth (CMT) disease in Campania, a region of Southern Italy. We analyzed a cohort of 197 index cases and reported the type and frequency of mutations for the whole CMT population and for each electrophysiological group (CMT1, CMT2, and hereditary neuropathy with susceptibility to pressure palsies [HNPP]) and for familial and isolated CMT cases. Genetic diagnosis was achieved in 148 patients (75.1%) with a higher success rate in HNPP and CMT1 than CMT2. Only four genes (PMP22, GJB1, MPZ, and GDAP1) accounted for 92% of all genetically confirmed CMT cases. In CMT1, PMP22 duplication was the most common mutation while the second gene in order of frequency was MPZ in familial and SH3TC2 in isolated cases. In CMT2, GJB1 was the most frequent mutated gene and GJB1 with GDAP1 accounted for almost 3/4 of genetically defined CMT2 patients. The first gene in order of frequency was GJB1 in familial and GDAP1 in isolated cases. In HNPP, the majority of patients harbored the PMP22 gene deletion. The novelty of our data is the relatively high frequency of SH3TC2 and GDAP1 mutations in demyelinating and axonal forms, respectively. These epidemiological data can help in panel design for our patients' population.